Guided-mode resonance and field enhancement in semiconductor nanorod arrays. Issue 1728 (21st April 2015) - Yu, W. X.; Yi, Y.
ABSTRACT: Guided mode resonance was numerically demonstrated in the tapered silicon nitride nanorod arrays on glass substrate. Finite difference time domain technique was employed to investigate the detailed light-matter interaction dynamics and the generation of resonance at femtoseconds. Enhanced electromagnetic (EM) field intensity with enhancement factor of 200∼250 could be achieved. This highly concentrated electromagnetic field could be extended to the nanorod array tips and substrate for higher order resonance modes, which allows future application of this transverse propagating field in optical signal amplification, like fluorescence or Raman enhancement.